2016
DOI: 10.1177/1535370215622584
|View full text |Cite
|
Sign up to set email alerts
|

Featured Article: Differential regulation of endothelial nitric oxide synthase phosphorylation by protease-activated receptors in adult human endothelial cells

Abstract: Protease-activated receptors have been shown to regulate endothelial nitric oxide synthase through the phosphorylation of specific sites on the enzyme. It has been established that PAR-2 activation phosphorylates eNOS-Ser-1177 and leads to the production of the potent vasodilator nitric oxide, while PAR-1 activation phosphorylates eNOS-Thr-495 and decreases nitric oxide production in human umbilical vein endothelial cells. In this study, we hypothesize a differential coupling of protease-activated receptors to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Thus, extensive unbiased and enhanced sampling MD simulations could provide additional insight, at the atomic level, into the numerous questions about the inner structural organization of NOSred, such as: i) What are the mechanisms of NOSred activity modulation by the regulatory elements? ii) Which structural changes are induced by PTMs in this domain (including phosphorylation of several serines in cNOSs, phosphorylation of Thr 495 and S -glutathionylation of Cys 689 and Cys 908 in eNOS [ 81 , [104] , [105] , [106] ])? iii) Are the regulatory mechanisms of the NOS isoforms different?…”
Section: Nos Structurementioning
confidence: 99%
“…Thus, extensive unbiased and enhanced sampling MD simulations could provide additional insight, at the atomic level, into the numerous questions about the inner structural organization of NOSred, such as: i) What are the mechanisms of NOSred activity modulation by the regulatory elements? ii) Which structural changes are induced by PTMs in this domain (including phosphorylation of several serines in cNOSs, phosphorylation of Thr 495 and S -glutathionylation of Cys 689 and Cys 908 in eNOS [ 81 , [104] , [105] , [106] ])? iii) Are the regulatory mechanisms of the NOS isoforms different?…”
Section: Nos Structurementioning
confidence: 99%
“…It has been reported that PAR2 activation leads to vasodilation of dural arteries in rodents and this in part is mediated by modulation of NO [ 17 , 24 ]. PAR2 has also been shown to increase NO production in multiple cell types via activation of NO synthase [ 24 26 ]. We have previously shown that PAR2 both promotes prostaglandin E2 (PGE2) production and increases sensitivity to PGE2 associated with transition to the chronic pain state [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that PAR-2 deficiency increased the phosphorylation and expression of eNOS in vivo after the injection of C48/80. PAR-2 has been reported to be expressed in endothelial Although some reports have shown that PAR-2 activation results in the phosphorylation of eNOS at Ser1177 in human endothelial cells and rat aorta with metabolic syndrome [29][30][31], another study reported that PAR-2 suppressed eNOS phosphorylation at Ser1177 in the aorta of diabetic mice [32].…”
Section: Discussionmentioning
confidence: 99%